Distal radius fracture volar locking plate osteosynthesis using wide-awake local anaesthesia. (October 2020) - Dukan, Ruben; Krief, Elie; Nizard, Remy
Surgical fixation of distal radius fractures under local anaesthesia with the patient wide awake allows an intraoperative testing of the fixation stability under active mobilization. We evaluated the feasibility and clinical results of this technique in 45 patients prospectively in two matched comparable groups: wide-awake local anaesthesia no tourniquet and loco-regional anaesthesia. We found that the pain scores during the anaesthetic administration and the surgical procedure were similar in two groups. Ranges of wrist motion and QuickDASH scores were improved significantly in the wide-awake local anaesthesia no tourniquet group at 6 weeks and 3 months and similar at 6 months compared with those receiving loco-regional anaesthesia. Patients in wide-awake local anaesthesia no tourniquet returned to work significantly earlier than the loco-regional anaesthesia group. We conclude that osteosynthesis of distal radius fractures can be safely performed under wide-awake local anaesthesia no tourniquet, leading to no increase in pain level and similar functional outcomes compared with those under loco-regional anaesthesia. Level of evidence: III